Repolarization in perfused myocardium predicts reperfusion ventricular tachyarrhythmias - Bernikova, Olesya G; Sedova, Ksenia A; Arteyeva, Natalia V; Ovechkin, Aleksey O; Kharin, Sergey N; Shmakov, Dmitry N; Azarov, Jan E (Journal of electrocardiology, 2018)
BACKGROUND: Aim of the study was to find out which myocardial repolarization parameters predict reperfusion ventricular tachycardia and fibrillation (VT/VF) and determine how these parameters express in ECG. METHODS: Coronary occlusion and reperfusion (30/30min) was induced in 24 cats. Local activation and end of repolarization times (RT) were measured in 88 intramyocardial leads. Computer simulations of precordial electrograms were performed. RESULTS: Reperfusion VT/VF developed in 10 animals. Arrhythmia-susceptible animals had longer RTs in perfused areas [183(177;202) vs 154(140;170) ms in susceptible and resistant animals, respectively, P<0.05]. In logistic regression analysis, VT/VFs were associated with prolonged RTs in the perfused area (OR 1.068; 95% CI 1.012-1.128; P=0.017). Simulations demonstrated that prolonged repolarization in the perfused/border zone caused precordial terminal T-wave inversion. CONCLUSIONS: The reperfusion VT/VFs were independently predicted by the longer RT in the perfused zone, which was reflected in the terminal negative phase of the electrocardiographic T-wave.
Keywords: Animals; reperfuzní poškození; Tachycardia, Ventricular; Simulation; ECG; fibrilace komor; Electrocardiography; elektrokardiografie; Cats; Arrhythmias; Repolarization; modely nemocí na zvířatech; Ischemia-reperfusion; Reperfusion Injury; Ventricular Fibrillation; komorová tachykardie; Disease Models, Animal; zvířata; kočky